Prevalence and Factors Associated with Dental Caries among Children and Adults in Selected Districts in Uganda - Kutesa, Annet; Kasangaki, Arabat; Nkamba, Moses; Muwazi, Louis; Okullo, Isaac; Rwenyonyi, Charles Mugisha (African Health Sciences, 2015)
The aim was to determine the prevalence and factors associated with dental caries among adults and children in seven districts of Uganda.Participants aged 11-13 (n=1230) and 35-44 years (n=648) were randomly selected from urban and rural areas of Gulu, Soroti, Jinja, Masaka, Kabale, Kabarole and Hoima districts. They were examined by 4 trained and calibrated dentists for dental caries using Decayed, Missing and Filled teeth index as described by World Health Organisation.Overall mean DMFT score was 0.73 for children and 4.71 for adults. Generally, there was a higher mean DMFT score in the rural (2.19) compared to urban areas (1.97). In all the districts, except Hoima, there was a higher mean DMFT score of children in rural compared to urban. In adults, similar trend was mainly registered in Masaka, Hoima and Gulu districts. Most participants (79.9%, n=1309)occasionally ate sugared snacks. Overall, 95% (n=1795) of the participants cleaned their teeth with plastic tooth brushes (71.7%) and chewing sticks (8.3%).Although the severity of dental caries was low, the disease was widespread in the study population. A high proportion of participants reported consumption of sugared snacks and drinks, which calls for oral health education.
Keywords: Dental caries prevalence, severity, sugared snacks, tooth brushing, Uganda